PENGARUH EFEKTIVITAS PENGGUNAAN INTERNET TERHADAP HASIL BELAJAR SISWA KELAS X TEKNIK GAMBAR BANGUNAN SMKN 26 JAKARTA PADA MATA PELAJARAN ILMU BAHAN BANGUNAN - Putri Indrawati; Tuti Iriani; Amos Neolaka (Jurnal Pensil : Pendidikan Teknik Sipil, 2012)
This study aims to determine the effectiveness of using the Internet to influence student learning outcomes SMKN 26 Jakarta class X drawing technique building in science subjects of building materials. View the content of learning materials Building Materials Sciences that quite a lot, plus the allocation of limited time, giving the task done. Granting duty if selected as a method of teaching learning material much out of balance with the available time. Giving the task is done by utilizing the Internet (search engines, facebook and email). The sample in this study a number of 55 students. The results were positive and there is a relationship between the effectiveness of using the internet signifkan of student learning outcomes with a relatively low level of relationship